The British Late Victorian Societyâs Contradictory Responses Towards Extraordinary Phenomena As Reflected in Doyleâs The Hound of the Baskervilles - , ARRIENDA RIZKY D.W., Dra. Esmeraldayanti Sosronegoro, S.U. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
This graduating paper discusses strange phenomena around the death of an important figure in a certain rural-agricultural area in Great Britain. The phenomena are believed to have close relatioship with a legend about an enormous black ghost dog which existed within British late Victorian era society. In addition, this paper also presents the way of thinking and attitude of the industrial society and the rural-agricultural society in Great Britain during the late Victorian era. Mimetic approach is applied in this graduating paper to provide evidence of how the novel to a certain extent reflects the legend about the black ghost dog which existed within Great Britain, and also the differences in the ways of thinking and attitude towards the phenomena considered as supernatural. Moreover, in order to explain why such differences in viewing a particular legend exist, Sudjarwaâs theory on cultural lag in addition to Dysonâs theory on the factors causing inter cultural similarities and differences are also applied. The results show that the legend about hellhounds or blackdogs as presented in the novel is common throughout areas in Great Britain. The creature is called by different names in different areas. Furthermore, the results also show that the two types of society have different ways of thinking and attitudes towards the phenomena. Even within the industrial society itself, different ways and attitudes can also be found towards the same phenomena. These reflect to a certain extent the paradoxical conditions within the British society during the late Victorian era. Besides, geographical factor, historical factor, and different views of life also cause the differences to happen.